Production of fermentable sugar from red seaweed by chemical and enzymatic hydrolysis - Nor Amira Syahida Bt. Mohd. Radzi (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Red seaweed is a third generation biomass which offering several advantages over lignocellulosic biomass. Therefore, in order to evaluate the applicability of red seaweed as a potential biofuel resources, optimization of chemical hydrolysis and enzymatic hydrolysis were done to produce fermentable sugar from red seaweed. Pretreatment by chemical hydrolysis was carried out with different sulfuric acid concentrations and reaction temperature (80 oC - 99 oC) by using water bath. Optimal pretreatment conditions were determined at 99 oC using 0.06 % v/v sulfuric acid with maximum 18.06 % sugar content with yield of 5.42 g/L sugar produced. Further saccharification process were done to improve the yield of fermentable sugar in the sample. Hence, enzymatic hydrolysis was performed by addition of cellulase enzyme by 0.01 mL - 0.04 mL of enzyme. A maximum reducing sugar concentration of 8.14 g/L fermentable sugar with yield of 0.27 g sugar/g biomass. These results indicates that the chemical hydrolysis and enzymatic hydrolysis is economical and able to produce higher fermentable sugar with the usage of correct materials and method.